Physiological response of CmWRKY15-1 to chrysanthemum white rust based on TRV-VIGS - Chen, Qi; Kuang, Anchan; Wu, Haihong; Liu, Di; Zhang, Xin; Mao, Hongyu (Frontiers in Plant Science, 2023)
Chrysanthemum White Rust (CWR) caused by Puccinia horiana Henn. is a major disease in the production process of chrysanthemum, which is widely spread all over the world and can be called “cancer” of chrysanthemum. To clarify the disease resistance function of disease resistance genes can provide a theoretical basis for the utilization and genetic improvement of chrysanthemum resistant varieties. In this study, the resistant cultivar ‘China Red’ was used as the experimental material. We constructed the silencing vector pTRV2-CmWRKY15-1 and obtained the silenced line named TRV-CmWRKY15-1. The results of enzyme activity after inoculation with pathogenic fungi showed that the activities of antioxidant enzymes SOD, POD, CAT and defense-related enzymes PAL and CHI in leaves were stimulated under the stress of P. horiana. In the WT, the activities of SOD, POD and CAT at the peak value were 1.99 times, 2.84 times and 1.39 times higher than that in TRV-CmWRKY15-1, respectively. And the activities of PALand CHI at the peak were 1.63 times and 1.12 times of TRV-CmWRKY15-1. The content of MDA and soluble sugar also confirmed that chrysanthemum was more susceptible to pathogenic fungi when CmWRKY15-1 was silenced. The expression levels of POD, SOD, PAL and CHI at different time points showed that the expressions of defense enzyme related genes were inhibited in TRV-WRKY15-1 under the infection of P. horiana, which weakened the ability of chrysanthemum to resist white rust. In conclusion, CmWRKY15-1 may increased the resistance of chrysanthemum to white rust by increasing the activity of protective enzyme system, which laid a foundation for breeding new varieties with disease resistance.